2012
DOI: 10.1002/adsc.201200677
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Naltrexone by Palladium‐Catalyzed N‐Demethylation/Acylation of Oxymorphone: The Benefit of CH Activation and the Intramolecular Acyl Transfer from C‐14 Hydroxy

Abstract: Oxymorphone was converted to naltrexone in three steps by palladium-catalyzed oxidative N-demethylation and intramolecular acyl transfer from C-14 hydroxy to N-17. Vitride reduction of N-acylamide to N-alkylamine proceeded with concomitant reductive deprotection of C-6 and O-3 functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…However, they were also highly dependent on the substituent present at C6, with more electron withdrawing substituents giving lower product yields. Overall, oxidations of opioids are challenging and almost exclusive to the production of 14-hydroxy derivatives from thebaine (6) and oripavine (7), in route to the preparation of drugs such as naloxone (4) and naltrexone (5) (Figure 1) [19,29]. Nonetheless, some oxidized products of opioids, namely 7,8-epoxides, have been suggested to bear less liability to dependence, with activity comparable to the parent compounds both in vitro and in vivo [23,24].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, they were also highly dependent on the substituent present at C6, with more electron withdrawing substituents giving lower product yields. Overall, oxidations of opioids are challenging and almost exclusive to the production of 14-hydroxy derivatives from thebaine (6) and oripavine (7), in route to the preparation of drugs such as naloxone (4) and naltrexone (5) (Figure 1) [19,29]. Nonetheless, some oxidized products of opioids, namely 7,8-epoxides, have been suggested to bear less liability to dependence, with activity comparable to the parent compounds both in vitro and in vivo [23,24].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[5][6][7] The residence time is kept constant by using higher flow rates, which involves ap otential change in superficial velocity. [45] Based on the pioneering work of Hudlicky, [46] the aforementioned consortium has developed environmentally friendly continuous-flow procedures for catalytic N-demethylation methods (11!12)t hat rely on the use of molecular oxygen ast erminal oxidant (Scheme 8). One approach to overcome this problem is to apply "smartd imensioning" by using the appropriate reactor modules at the right locations.…”
Section: Ideal Solventsmentioning
confidence: 99%
“…With 10 mol‐% Pd(OAc) 2 as catalyst and dioxane/acetic anhydride as solvent, N ‐acetylnorhydrocodone was obtained after 15 h at 80 °C. In subsequent publications, the Hudlicky group showed that the reaction can be extended to certain other morphine alkaloids, such as 3,14‐diacetyloxymorphone, by using oxygen under atmospheric pressure ( 5 ; Scheme ) , . The demethylation of diacetyloxymorphone is accompanied by intramolecular 14‐ O ‐ to 17‐ N ‐acetyl migration to form the 3,17‐diacetylnoroxy derivative as the immediate product ( 7 ; Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent publications, the Hudlicky group showed that the reaction can be extended to certain other morphine alkaloids, such as 3,14‐diacetyloxymorphone, by using oxygen under atmospheric pressure ( 5 ; Scheme ) , . The demethylation of diacetyloxymorphone is accompanied by intramolecular 14‐ O ‐ to 17‐ N ‐acetyl migration to form the 3,17‐diacetylnoroxy derivative as the immediate product ( 7 ; Scheme ) . Subsequent hydrolysis with 6 m HCl finally yields the desired noroxymorphone ( 3a ; Scheme ) …”
Section: Introductionmentioning
confidence: 99%